In vivo visualization of single native pancreatic islets in the mouse. (November 2013) - Balla, Dávid Z.; Gottschalk, Sven; Shajan, G.; Ueberberg, Sandra; Schneider, Stephan; Hardtke‐Wolenski, Matthias; Jaeckel, Elmar; Hoerr, Verena; Faber, Cornelius; Scheffler, Klaus; Pohmann, Rolf; Engelmann, Jörn; et al.
<x xml:space="preserve">Abstract</x> The purpose of this study was to investigate the potential of a novel targeted contrast agent (CA) for the in vivo visualization of single native pancreatic islets, the sites of insulin production, in the pancreas of mice using magnetic resonance imaging (MRI). The CA for intravenous administration was composed of the β‐cell‐specific single‐chain antibody fragment, SCA B1, and ferromagnetic carbon‐coated cobalt nanoparticles. MRI experiments were performed at 7, 9.4 and 16.4 T in excised organs (pancreas, liver, kidney, spleen), at 7 T in mice fixed in formalin and at 9.4 and 16.4 T in living mice. Image contrast in untreated control animals was compared with images from mice treated with unspecific and specific CA. For the validation of MRI results, selected pancreases were subjected to immunohistochemical staining and numerical contrast simulations were performed. Ex vivo results and the outcome of immunohistochemistry suggest that islets are marked only by the CA containing SCA B1. Strong accumulation of particles was found also in other investigated organs owing to the uptake by the reticuloendothelial system, but the contrast in the MR images is clearly distinguishable from the islet specific contrast in pancreases and numerical predictions. In vivo experiments based on averaged dynamic sampling with 66 × 66 × 100 µm3 and triggered acquisition with 90 × 90 × 200 µm3 nominal resolution resulted in similar particle contrast to in in vitro measurements. The newly developed CA and MRI strategies have the potential to be used for studying mouse diabetes models by visualizing single native pancreatic islets. Copyright © 2013 John Wiley & Sons, Ltd.